The Utilization of Comic Strips for Educating Reading Skills in Primary School - Ni Luh Kadek Wiwik Kartika Dewi (Jurnal Penelitian Mahasiswa Indonesia, 2023)
Primary school is one of the school levels that learn English. There are four English language skills, those are listening, speaking, reading, and writing. one of the important skills is reading because it is a basic skill that primary school students have to master due to the lot of information and knowledge can students get through reading. The use of various media can be utilized by teachers to support the learning process, such as comic strips. A comic strip is media that contains images, text, and other visualization to tell information in the form of a story. This research aims to implement a comic strip for educating primary school students’ reading skills and also expand their vocabulary. The result shows that the utilization of comic strips helps teachers to facilitate and support the students to enhance their reading skills. In addition, the utilization of comic strips as learning media is useful to enhance reading skills at any level for students.